Socio Entrepreneurship: Tinjauan Teori Dan Perannya Bagi Masyarakat - Ratna Widiastuti .; Meily Margaretha . (Universitas Kristen Maranatha, 2011)
This paper tries to give the literature review of the socio entrepreneurship concept such as the historical background of socio entrepreneurship, characteristics to be a socio entrepreneurship. Socio entrepreneurship is viewed as an entrepreneur who social driven, to create superior value for the society. This concept has developed from many universities. Socio entrepreneurs differ from business entrepreneurs in terms of their mission; the social mission is explicit and central. The obstacles to implement socio entrepreneurship and the role of socio entrepreneurship for the society are also discussed in this paper. The last discussion focused on the examples of people or organization who successfully implement this concept on their business activity.Keywords: socio entrepreneurship, society, entrepreneur.